Protocol to implement nutritional interventions for the management of childhood obesity in Primary Health Care - Silva, Chrisllayne Oliveira da; Pereira , Francisco Gilberto Fernandes; Claro, Maísa de Lima; Sousa, Artemizia Francisca de; Silva, Danilla Michelle Costa e; Lima, Luisa Helena de Oliveira (Revista de Enfermagem da UFPI, 2023)
Objective: To create and validate a protocol to implement nutritional interventions for the management of childhood obesity in the Primary Health Care scope. Methods: This is a methodological study organized into three phases: elaboration of a systematic review of the “overview” type using the PRISMA recommendations; preparation of the clinical protocol; and content validation using the AGREE II and AGREE-REX instruments. Results: A total of 17 studies were included to create the protocol, indicating effectiveness in interventions with outcomes in a significant BMI reduction, change in eating behaviors and habits, and increase in the knowledge level about healthy eating. The clinical protocol assessment obtained a score >70% and, according to the parameter used (≥50% high quality), it was considered adequate for implementation in the children’s health field, more specifically in the management of childhood obesity. Conclusion: A care protocol for the management of childhood obesity in the Primary Health Care scope positively represents a sustainable and flexible strategy with performance of several social actors such as health professionals and family members, among others, contributing to reducing risks of comorbidities associated with obesity and health costs, as well as to promoting healthier behaviors in the pediatric population.